PENGARUH PENCAHAYAAN, POSISI KERJA DAN GENDER TERHADAP PRODUKTIVITAS VISUAL INSPECTION TASK - Yanti Pasmawati; Christofora Desi Kusmindari; Paulus Sukapto; Johanna Renny Octavia (Universitas Katolik Parahyangan, 2017)
Visual inspection task is the inspection activity of a product with the eye position centered over the moving conveyor, the faster the product is produced, the more critical the time of the inspection operator. The conditions in the long term will result in a decrease in productivity (Manuaba, 1992). The research objective to be achieved, among others: (1) Determining the optimal level of productivity based on the studies measure of performance checks on experimental design in every visual inspection task beverage packaging cup